(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Shigellosis (bacterial dysentery) is an anthroponotic infectious disease with a fecal-oral transmission mechanism. It is caused by bacteria of the genus Shigella, and occurs in acute and chronic forms. It is characterized by manifestations of general intoxication with fever and signs of inflammation of the gastrointestinal tract (mainly the distal colon in the form of spastic hemocolitis).